Population heterogeneity of upland rice in northern Thailand - Karladee,D. (Faculty of Agriculture, Kasetsart University Chatuchak, 2015)
Landraces upland rice have low productivity, in northern Thailand; averaging only 0.9 t ha-1. The cultivation gains a low input system, the fluctuation environment, the less crop protection, the genetic potential to utilize higher input and the heterogeneity in the rice populations may also factors causing these low yields. This study was to quantify the extent of genotype heterogeneity within the upland rice populations. Rice panicles were sampled in farmers' fields prior to harvesting. Heterogeneity was identified as variation in colors of husk, levels of grain amylose and variation in the ratio of decorticated grain length to width. Grain yield was calculated. Results showed that average estimated yield based on grain filling in farmers' field was 1.16 t ha-1. Percent of unfilled spikelets was high (42.61% on average) and suspected to be a major factor in lowering the grain yield in the area. By contrast, panicle density was medium (PANO=90) and grain weight was high (Wg=31.6 g). Grain production was potentially as high as 1.72 t ha-1 if the filled spikelets percentage was 85%, as in the standard lowland rice. The mixture of indica and japonica types most likely explains the high proportion of unfilled spikelets because the japonica is thermosensitive, and will flower approximately a month later than indica. Purification of this heterogeneity may be needed to improve grain yield. The improvement should be base carefully upon the villagers' wisdom, culture and traditions. The results contrast with the studies that have reported on the advantage of genetic diversity in landrace varieties of upland rice, and suggest that a significant yield penalty maybe an outcome of such diversity in some circumstances.